An investigation into the relationship between smash factor and swing weight for golf club fitting - Foong, Yung Chieh. (2012)
The purpose of this project is to investigate the relationship between smash factor and swing weight. This is first time by taking the swing weight as a key parameter to optimise the smash factor in order to maximize the driving distance. A set of shafts weight from 56g, 63g, and 70g were evaluated which executed by ten golfers. In order to investigate the relationship of swing weight the shaft flex is control within frequency range from 242cpm to 244cpm to reduce the probability that the shaft flex that influenced the result. A launch monitor Trackman flight scope is used to provide the swing data of each golfer. A photographic method to get the swing tempo data is implemented in this project. The process of investigate the relationship between these two factor is by using the swing tempo ratio to determine how the swing weight affecting it.